Developing Destination Brand Identity: Towards sustainability of tourism destination from the perspective of stakeholders and theory of social identity - Musa, Norfardilawati; Md Noor, Shuhaida; Mohamad, Wardah (2013)
This is a conceptual paper on the concept of destination brand identity from the perspective of stakeholders. In planning and strategising for sustainable tourism destination, destination branding is a critical issue that needs to be explored. The nature of a destination domain is one where there exists an “open-system” of interdependent, multidimensional and multiple stakeholders where the actions of one stakeholder will impact the rest of the actors in the destination, thus making the process of developing destination identity very complex. The difficulties in dealing with different interests amongst the stakeholders make the process of developing destination identity more complicated, resulting in difficulties in achieving unity and understanding about the "shared image" for a destination brand. Moreover, to produce a sustainable tourism destination, the supports offered by stakeholders to the planning and development process is a key element for the successful operation, management and sustainibility of the destination. The destination branding literature shows consistency in the consideration of the power of stakeholders for branding destination. Therefore, based on the theory of stakeholders and the theory of social identity that underlies this paper, the study will identify the relationship between the stakeholders and brand development for a destination domain. This paper introduces a framework designed to study the implications of stakeholders towards the destination brand.